TANTANGAN DAN PELUANG MAHASISWA MAGANG DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK DI SMP PLUS JA-ALHAQ KOTA BENGKULU - Saepudin, Saepudin; Salsabila, Shafa; Juliantari, Daniati; Rinanda Puppri, Karista (FAKULTAS TARBIYAH UNIVERSITAS QOMARUDDIN GRESIK - JAWA TIMUR, 2025)
The internship program is an integral part of education for education program students which aims to develop teaching skills and understand the dynamics of the world of education. This research aims to analyze the challenges and opportunities faced by intern students at SMP Plus Ja-Alhaq, Bengkulu City in developing their pedagogical competencies. This research uses a descriptive qualitative approach with data collection techniques in the form of direct observation, interviews and document analysis. The research results show that intern students face several main challenges, such as limited teaching experience, classroom management, and adaptation to the school environment. However, internship programs also provide great opportunities to develop pedagogical skills, such as guidance from professional teachers, direct experience in teaching, and development of communication skills. It is hoped that this internship experience can improve the quality of students' teaching and strengthen their competence as prospective educators who are ready to face challenges in the world of education.